O processo de expansão urbana e seu impacto na cobertura vegetal de Macapá - COSTA, Luciana Castro Serafim (Universidade Federal de Pernambuco, 2022)
A growing urban population fears the need for city expansion, causing non-environmental transformations, capable of creating its own microclimate, which can form heat pipes. The purpose of this work is to analyze the urban expansion process in the Macapá Headquarters District, Capital of the State of Amapá, located in the Brazilian Amazon and the non quantitative impact of vegetation cover. The applied methodology is derived from the analysis of two popular data from 1960 to 2010, made available by the Brazilian Institute of Geography and Statistics and analysis of the growth of urban area and its non-quantitative impact of vegetation cover in the period from 1985 to 2015, using the classification Supervised by Maximum Likelihood in satellite images. The results obtained are based on the fact that from 1960 to 2010 or population increase in the State of Amapá, in order to concentrate a greater part of the population in urban areas, mainly in the Capital, it has 59.47% of the state population, being that 93% of the population of Macapá resides not district headquarters. An analysis of the images from 1985 to 2015 shows that an urban area tripled in this period, causing a decrease of 48.91% of closed and 17.13% of vegetation. The period of greatest loss occurred between the years 1985 and 1993, confirming that the vegetation cover of the Macapá headquarters district had been directly impacted by the growth of the city. Reflection on the reduction of green areas and loss of environmental quality related to the microclimatic factors performed by urban vegetation.